Uma cartografia bibliográfica da terapia ocupacional social sobre a temática da juventude negra - Ribeiro, Rovana Patrocinio (2021)
This dissertation seeks to describe from the point of view of Social Anthropology and the meanings of the youth and race category as emerging elements of the intellectual field of Social Occupational Therapy. Through a bibliographic analysis of the tensions constituting the racial theme in social thought, we seek to focus on such processes in that disciplinary field, their tendencies, main actors and particular uses, highlighting the obstacles to the inclusion of the racial theme as a center of analysis and not just as a vicinal effect of poverty. It is concluded that between government action through institutional projects and the search for autonomy through activities such as METUIA Projects, the knowledges and actions of such professionals are outlined and the new directions of professional and academic approaches.